2020
DOI: 10.3390/molecules25204795
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Green Synthesis of Chitosan and Zinc Oxide Nanoparticles with Strong Antibacterial Activity against Rice Pathogen Xanthomonas oryzae pv. oryzae

Abstract: Bacterial leaf blight caused by Xanthomonas oryzae pv. oryzae (Xoo) is one of the most devastating diseases, resulting in significant yield losses in rice. The extensive use of chemical antibacterial agents has led to an increase the environmental toxicity. Nanotechnology products are being developed as a promising alternative to control plant disease with low environmental impact. In the present study, we investigated the antibacterial activity of biosynthesized chitosan nanoparticles (CSNPs) and zinc oxide n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
34
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 74 publications
(43 citation statements)
references
References 72 publications
8
34
0
1
Order By: Relevance
“…The SEM-EDS shows the elemental analysis of the nanoparticles contained only the element and oxygen which confirms the presence of the nanoparticles in the samples and its high purity. The elemental percentage of ZnONPs in this study is consistent with the reports of Abdallah et al (2020), while those of MnO 2 NPs and MgONPs are in agreement with the report of Ogunyemi et al (2019a). Upon the treatment with ZnO, MgO, or MnO 2 , the characteristic cell damage and leakage of cell content observed using TEM agrees with the reports of Stoimenov et al (2002), who reported the loss of distinctive cell membrane of Escherichia coli.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The SEM-EDS shows the elemental analysis of the nanoparticles contained only the element and oxygen which confirms the presence of the nanoparticles in the samples and its high purity. The elemental percentage of ZnONPs in this study is consistent with the reports of Abdallah et al (2020), while those of MnO 2 NPs and MgONPs are in agreement with the report of Ogunyemi et al (2019a). Upon the treatment with ZnO, MgO, or MnO 2 , the characteristic cell damage and leakage of cell content observed using TEM agrees with the reports of Stoimenov et al (2002), who reported the loss of distinctive cell membrane of Escherichia coli.…”
Section: Discussionsupporting
confidence: 92%
“…The absence of peaks in the bulk solutions of ZnO, MgO, and MnO 2 indicates the absence of nanoparticles in the bulk solutions which is consistent with the reports of Abdallah et al (2020). The UV peak of 385, 230, and 230 nm, respectively, for ZnO, MgO, and MnO 2 nanoparticles recorded in this study is consistent with our previous study of biosynthesis of MgO and MnO 2 nanoparticles (Ogunyemi et al, 2019a), while Abdallah et al (2019bAbdallah et al ( , 2020 recorded a different peak for ZnO and MgO nanoparticles. In the study of Salunke et al (2015), a peak of 365 nm was observed for MnO 2 nanoparticles.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations